2013
DOI: 10.1002/jmv.23860
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance mutations and genetic diversity in adults treated for HIV type 1 infection in Mauritania

Abstract: The aim of this cross-sectional study was to evaluate the drug resistance mutationprofile observed in patients receiving antiretroviral therapy with virological failure and to document the HIV-1 genetic diversity in Mauritania. Eighty-six subjects were included and 65 samples were amplified successfully and sequenced. HIV-1 genotyping was performed using the Agence Nationale de Recherche sur le SIDA AC11 resistance procedure. The median treatment duration was 32 months (range: 6-88) and the median viral load, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
3
5
0
Order By: Relevance
“…The life-threatening common viral diseases include HCV, HIV-1, SARS, MERS ( Middle East Respiratory Syndrome ) and mentioned above avian flu variants, e.g., H5N1 [ 31 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The reason of inefficient medications and vaccines include high virus mutation variability, its low specificity and avoiding the host immune response [ 55 , 57 , 59 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. It also must be remembered, that many of the existing antiviral drugs, cause side effects and may lead to the development of other diseases than initially treated.…”
Section: Aptamers In the Treatment Of Viral Infectionsmentioning
confidence: 99%
“…The life-threatening common viral diseases include HCV, HIV-1, SARS, MERS ( Middle East Respiratory Syndrome ) and mentioned above avian flu variants, e.g., H5N1 [ 31 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The reason of inefficient medications and vaccines include high virus mutation variability, its low specificity and avoiding the host immune response [ 55 , 57 , 59 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. It also must be remembered, that many of the existing antiviral drugs, cause side effects and may lead to the development of other diseases than initially treated.…”
Section: Aptamers In the Treatment Of Viral Infectionsmentioning
confidence: 99%
“…The increased use of antiretroviral therapy has reduced significantly the number of deaths related to HIV/AIDS and improved the life expectancy of people living with HIV. [10] It has been suggested that scaling up of ART results in a level of virological suppression at the population level that will reduce HIV transmission. [11][12][13][14][15] With the increased numbers of patients being treated, there is increased potential for development and spread of resistant virus.…”
Section: Discussionmentioning
confidence: 99%
“…[2,[22][23][24][25] Although HAART may limit the extent of selection during treatment, the success of HAART could still be compromised by the emergence of HIV drug resistance. [10,26] Resistance can be acquired as the pool of variants within the population increases. [19] Resistance to an antiretroviral drug class is defined by the presence of at least one primary resistance mutation (PRM), as included in the mutation list paneled by the International Antiviral Society in 2013 [27], within the genes for the nucleos(t)ide reverse transcriptase inhibitors (NRTIs), non nucleos(t)ide reverse transcriptase inhibitors (NNRTIs), and protease inhibitors (PIs).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the therapeutic of infectious diseases is mainly based on the principle of symptomatic treatment or specific anti-pathogen treatment. However, antimicrobial resistance, high viral genomes mutation variability and escaping the host immune response make most medications and vaccines inefficient ( Finlay and McFadden, 2006 ; Labella and Merel, 2013 ; Dunning et al, 2014a ; Fall-Malick et al, 2014 ; Ferir et al, 2014 ; Lazarevic, 2014 ; Marascio et al, 2014 ; Sahu, 2015 ; Wandtke et al, 2015 ). It is worth mentioning that the effect of antiviral therapy is not ideal for all patients and side effects caused by many existing antiviral drugs may lead to other diseases than primary affection.…”
Section: Application Of Aptamers In Infectious Diseases Treatmentmentioning
confidence: 99%